2022
DOI: 10.3390/agriculture12111753
|View full text |Cite
|
Sign up to set email alerts
|

Electric Heating System with Thermal Storage Units and Ceiling Fans for Cattle-Breeding Farms

Abstract: A combined energy–saving heat supply system was proposed that included a combined ETS unit and a ceiling fan, and provided the normative air parameters in a livestock room, with an air temperature of −17 °C and air relative humidity (ARH) of −75%. A heat supply system of a preventive maintenance premises for calves was chosen as the subject of the study. Comparative analysis of the temperature and ARH distribution with height in the preventive maintenance premises, was carried out, with and without a ceiling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous works of the authors were also devoted to modeling the thermal state of the heat storage elements of the electric thermal storage (ETS) [9] and calculating the thermal characteristics of the ETS [10]. The results of experimental studies of the thermal state of heat storage elements in the heat charging and heat emission operation modes of ETS are presented [11].…”
Section: Methodsmentioning
confidence: 99%
“…Previous works of the authors were also devoted to modeling the thermal state of the heat storage elements of the electric thermal storage (ETS) [9] and calculating the thermal characteristics of the ETS [10]. The results of experimental studies of the thermal state of heat storage elements in the heat charging and heat emission operation modes of ETS are presented [11].…”
Section: Methodsmentioning
confidence: 99%
“…Consumers are subject to the impacts of bio stimulants, which have an impact on their health. The organic Ugmax productionprocess dramatically increases the number of leaves, the length of the root, and the width of the root neck compared to the control variety in order to lessen the biochemical effects.In [34],author's have concluded that,Electric heating systems: Research into the heating-ventilation system used in cattle-breeding farm preventative maintenance buildings during the winter seasonhas revealed that using ceiling fans can shorten the time it takes for buildings to heat and cool. The usage of electric heating systems was reduced at the same time, which resulted in a drop in energy consumption.…”
Section: Futurementioning
confidence: 99%
“…Modern agriculture needs new methods and technologies of crop production. To increase plant productivity and yields, various measures are used: digital innovations in soil cultivation, new mineral fertilizers, and non-standard methods of growing agricultural crops [12][13][14]. The application of smart functional covering polymer materials and substrates for growing crops, especially in breeding, where the most expensive and valuable seed material is used, contributes to the development of the field of effective crop production [15,16].…”
Section: Introductionmentioning
confidence: 99%